1964
DOI: 10.1002/j.1556-6978.1964.tb00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Achievement in Counseling and Guidance Graduate Study

Abstract: While not an ultimate criterion of professional competence, acceptable academic performance in graduate school is a prequisite which the professional counselor must meet. Tests of academic ability have frequently been used to select prospective counselors; however, the validity of such tests for this specific task has not been well established. Of particular importance has been the lack of a uniform criterion of academic success for all members of a sample under investigation. How then do some of the commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1966
1966
1969
1969

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…There is no lack of information on the kind of persons counselor educators want in their programs. Studies such as those by Callis and Prediger (1964), Cody and Knock (1967), Cohen (1961), Dugan (1961), Hill and Green (1960), and Wasson (1965) have identified attitudes and competencies required for success in counselor preparation and for counselor practice. For example, Soper and Combs (1963) conducted a study in which they found that good counselors perceive from an internal rather than an external frame of reference and in terms of people rather than things.…”
mentioning
confidence: 99%
“…There is no lack of information on the kind of persons counselor educators want in their programs. Studies such as those by Callis and Prediger (1964), Cody and Knock (1967), Cohen (1961), Dugan (1961), Hill and Green (1960), and Wasson (1965) have identified attitudes and competencies required for success in counselor preparation and for counselor practice. For example, Soper and Combs (1963) conducted a study in which they found that good counselors perceive from an internal rather than an external frame of reference and in terms of people rather than things.…”
mentioning
confidence: 99%
“…(Hill, 1962;Stripling & Lister, 1963. ) Recent studies by Moore ( 1963), Blocher ( 1963), Callis &Prediger ( 1964), andDiUey ( 1963), have provided basic research in the area; however a number of important questions still remain unanswered. One of the most crucial of these questions for counselor educators is whether difFerent kinds of factors account for the success of male and female counselor candidates in counseling and guidance institutes.…”
Section: The Problemmentioning
confidence: 99%